1990
DOI: 10.1159/000235192
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin E Responses and Lung Pathology Resulting from Aerosol Exposure of Calves to Respiratory Syncytial Virus and <i>Micropolyspora faeni</i>

Abstract: Bovine respiratory syncytial virus (BRSV) infection of calves has been associated with a type-I hypersensitivity syndrome not unlike respiratory syncytial virus-associated pulmonary symptomatology in humans. To study the mechanism of pulmonary pathology in calves and define the relationship with both viral-specific IgE response and IgE titers to concurrent aerosol of Micropolyspora faeni (Mf) we subjected groups of calves to inhalation of Mf during acute BRSV infection. The calves were divided into 4 groups: e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

1994
1994
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 9 publications
1
10
0
2
Order By: Relevance
“…RSV-infected murine lungs were characterized by increased eosinophilia, cytokine production (including IL-4), and inflammation, including up-regulation of adhesion molecules and chemokines. Additionally, in a bovine model RSV infection has been shown to enhance sensitization to subsequent airway Ag (61,62). Although still controversial, a variety of studies suggest that individuals who suffered an RSV infection during childhood are significantly predisposed to develop allergy and atopy either during early adulthood or later (63)(64)(65)(66)(67)(68)(69)(70).…”
Section: Discussionmentioning
confidence: 99%
“…RSV-infected murine lungs were characterized by increased eosinophilia, cytokine production (including IL-4), and inflammation, including up-regulation of adhesion molecules and chemokines. Additionally, in a bovine model RSV infection has been shown to enhance sensitization to subsequent airway Ag (61,62). Although still controversial, a variety of studies suggest that individuals who suffered an RSV infection during childhood are significantly predisposed to develop allergy and atopy either during early adulthood or later (63)(64)(65)(66)(67)(68)(69)(70).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study we examined the effect of BRSV infection on aerosol exposure of naive and Micropolysporafaeni (Mf)-sensitized calves. We reported that the in halation of Mf during BRSV infection of previously Mf aerosol-sensitized calves enhanced virus-specific IgE pro duction and severity of pulmonary disease expression [10].…”
Section: Introductionmentioning
confidence: 90%
“…Some have shown that RSV bronchiolitis is more severe in the first case. In several experimental systems, allergen sensitization preceded infection by several weeks and then challenge took place during RSV infection (Gershwin et al, 1990;Gershwin and Giri, 1992;Barends et al, 2002;Lambert et al, 2003). These experimental systems employed allergens such as Micropolyspora faeni (currently known as Saccharopolyspora rectivirgula), Ovalbumin (OVA), or carbon black.…”
Section: Mechanisms Of Allergen Induced Rsv Immunomodulationmentioning
confidence: 99%